La résurgence/convergence du triptyque « catastrophe-résilience-adaptation » pour (re)penser la « fabrique urbaine » face aux risques climatiques - Béatrice Quenault (Développement Durable et Territoires)
Confronted with climate change, cities appear to be spaces at risk, not so much because of their exposure to climatic threats but rather because of their present and future vulnerabilities to such hazards taking into account their limited capacities to cope with or to respond to such events. This article attempts firstly to precise both the definition and the epistemological frame of resilience and its complex links with the afferent notions of vulnerability and adaptation in a context of ineluctable climatic disasters. It shows why the adoption of a systemic perspective, i.e. complex and dynamic, of resilience can offer a pertinent frame, under specific conditions, to envisage sustainable futures for urbanized territories faced with present and forthcoming climate risks. Secondly, considering the actual uses and meanings of resilience, this article interrogates the operational feature of this concept to re-think about the “urban fabric” in an integrated manner with the climate risks prevention. Finally, it aims to clarify why planned adaptation strategies aimed at reducing vulnerabilities and enhancing proactive resilience of cities, that have progressively become in both academic and institutional discourses a key feature, and even a tipping point, for urban sustainable development pathways, can revealed to be ambiguous.